Przemiany międzynarodowej mobilności Polaków = Changes in Poles’ level of international mobility - Wiśniewski, Rafał (1977– ). Autor; Komornicki, Tomasz. Autor (IGiPZ PAN, 2021)
Until very recently at least, modern society has been characterised by its increased mobility in both the short and long terms. Furthermore, this has been true of both domestic and international trips. The latter kind of mobility is addressed in the present article, which aims to cover relevant changes as they affected Polish people through the 2007‑2017 period. Against that background, particular attention has been paid to modal split in border traffic, with the changes involved presented in relation to supply with infrastructure and transport services. The article uses author’s own data, from research taking in a representative group of 1000 Polish adults (with the sample adjusted appropriately in relation to gender, and membership of the 18‑29, 30‑44, 45‑59 and 60 and over age groups, as well as place of residence: be that village, town of up to 50,000 inhabitants, city of 50‑200,000 inhabitants, city of more than 200,000 inhabitants, and Warsaw). The analysis did not encompass border areas, given the specific nature of the traffic there (and in this way it was possible to eliminate a large part of the daily movement taking place internationally (for the purposes of work, shopping, etc.), but in truth now representing short-term mobility within a region resided in (or else daily mobility using the classification after Kaufmann, 2005). At the same time, by imposing no distance limitations except those relating to border areas, the study retained a capacity to approximate the international part of genuine short-term mobility beyond the region inhabited. Nevertheless, most of the flows under analysis can be regarded as corresponding with the long-distance travel documented in the subject literature. However, the limit value for this kind of journey is set variously, e.g. at 50 miles one-way (Dargay and Clark, 2012), 100 km (Nordenholz et al., 2017), or 100 miles (Mokhtarian et. al., 2001). The configuration of near-border units in Poland is such that the research detailed also takes in slightly shorter transfers, given a limit values of around 30‑50 km in one direction. The aforementioned consideration of changes affecting Poles’ international mobility took in: frequency of travel, target destination (direction), place of crossing of the state border (section of border crossed), modes of transport, motivation, and duration. The work took account of a few basic categories of motivations for travel, i.e. on business (in relation to both hired labour and work on a person’s own account), for the purposes of education, tourism and holiday-related, visits to family and friends (thus treated as a motivation distinct from tourism) and shopping-related (usually in connection with small-scale border trade based around single-day visits). The work was carried out in 2018, but in relation to the years 2007 and 2017. 2007 is a targeted choice, with this being the last year before Poland’s Schengen Zone accession, hence a likely influence on both the dimensions and structure characterising international mobility. Research was done using the CATI method. The subjects of analysis were numbers of instances of international travel engaged in (as opposed to the numbers of people participating in transboundary flows). The work revealed an increase in the foreign mobility of Poles. The main motivator here was tourist travel and visits, as followed by goals associated with professional work and the visiting of family and friends. The modes of transport utilised most frequently were the aeroplane or private car, albeit with the former the subject of a major increase in share, even as the latter declined slightly in proportionate terms. There was a considerable reduction in the amount of travel achieved by coach (bus). At the time of study, Poles’ main destination countries for trips taken (under all motivations combined) were Germany, Czechia and Spain. Travel by Poles to eastern neighbour countries accounts for a very small share of all movement.
24 cm
Keywords: mobility; international travel; modal split; models of transport; travel motivations